Evidence of state-level variability in the economic and demographic well-being of people with disabilities in India - Nidhiya Menon; Susan L. Parish; Roderick A. Rose (Institute for the Study of Labor (IZA), 2011)
Among countries with comparable levels of income, India has one of the more progressive disability policy frameworks; however, people with disabilities in India are subject to multiple disadvantages. This paper focuses on state-level variations in outcomes for people with disabilities to provide one explanation for the stark contrast between the liberal laws on paper and the challenges faced by people with disabilities in practice. Using a random coefficients model that allows for state-level differences, we find that households with members with disabilities have 4.2 percent lower marriage rates, monthly per capita expenditure that is lower by 176 Indian Rupees (19 percent of overall average per capita expenditure), and about a 5 percent lower level of completed formal schooling as compared to households without disabled individuals. Tests of parameter constancy across states are almost uniformly rejected indicating the presence of substantial state-level heterogeneity across all models in the outcomes examined.
urn:nbn:de:101:1-201201113891
Keywords: O12; I15; I18; 330; disability; India; economic well-being; state variations; people with disabilities; Behinderte; Lebensqualität; Behindertenpolitik; Teilstaat; Indien